A Follow Up on Biochemical Parameters in Dengue Patients Attending BIRDEM Hospital (Ibrahim Medical College Journal, 2009)
During a one-year period between January to December 2002, a total of 84 cases were clinically diagnosed as dengue in the medical unit I of BIRDEM. They were classified into 4 groups: dengue fever (28), DHF-I (31), DHF-II (17), and DHF-III (8). Amongst the patients, 52 (61.9%) were males and 32 (38.1%) were females. SGPT and SGOT were above normal cutoff (40 IU) points in 64 (76.2%) and 73(86.9%) cases respectively. SGOT was higher than SGPT in most cases. S. Bilirubin was almost normal in all cases. S. Calcium level was low in a significant number of cases. Mean S. Ca was 8.69 ± 0.68 in case of DF and lower, i.e. 7.83 ± 0.66 in DHF-III. Mean Hb% also correlated with severity, i.e. 13.3 (SD ± 1.6) in DF and 14.8 ± 1.3 in DHF-III. ESR was lowest in DHF-III. Anti dengue IgM and IgG were done on 58 cases; 41 (70.7%) were IgM positive while 37 were positive for IgG. Ibrahim Med. Coll. J. 2008; 2(1): 25-27 Key words: Dengue, biochemical parameters, hospitalized patients.   doi: 10.3329/imcj.v2i1.2928